‘Not Too Hot, Not Too Cold, Just Right’: Empathetic Communication of Indonesian Big Brands through YouTube during the COVID-19 Pandemic - Jandy E. Luik; Agusly Irawan Aritonang (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2024)
This article is based on an exploratory study of YouTube videos related to the COVID-19 pandemic released by the official accounts of several big brands in Indonesia. By analyzing the videos released by these companies, a combination of key messages that are professionally conveyed to present the actions taken by the brands, in response to the pandemic, with an empathetic feel was found. While there is ample evidence to map out the creative processes behind these videos, our findings show that the brands aim to cover up the techniques they employ in achieving their goals, such as the sending of excessively sympathetic messages. The findings of this study provide initial empirical evidence of Indonesian companies’ tendency to assimilate the local culture of mutual assistance and the existence of branding activities that continue to be carried out during the pandemic. This article ends with a discussion of the communication processes carried out by commercial entities in challenging times.